A psychometric study of the team psychological safety scale and sport psychological safety inventory in Swedish elite sports - Carolina Lundqvist; Stéphane Bermon; Toomas Timpka (Scientific Reports)
Abstract Studies investigating psychological safety in sports and non-sports contexts have mostly utilized the universal Team Psychological Safety Scale (TPSS) aimed for performance development in professional teams. The Sport Psychological Safety Inventory (SPSI) has recently been introduced for psychological safety measurement specifically in sports. The aim of this study was to compare the psychometric properties of the TPSS and the SPSI within an elite sport context. A cross-sectional survey was used to collect data for assessment of the internal consistency, factorial validity, construct validity and measurement invariance of the TPSS and the SPSI. Complete data sets were provided by 371 elite Athletics athletes (track and field) and orienteers. Both the TPSS (ω = 0.72) and the SPSI subscales (range: ω = 0.81-0.88) showed acceptable internal consistency. Confirmatory factor analyses indicated a mediocre to good model fit for the TPSS and the SPSI three-factor correlated structure. The TPSS and the SPSI subscale ‘mentally healthy environment’ showed a moderate correlation. Measurement invariance tests suggested the TPSS to be fully invariant across genders, while the SPSI was found non-invariant. The study shows that the TPSS appears sound for assessing psychological safety in elite sports, while caution is needed when using the SPSI.